Perlindungan Hukum Bagi Konsumen Terhadap Pengguna Jasa ShopeeFood Ditinjau Dari Undang- Undang Perlindungan Konsumen - Widyasari, Dini; Iskandar, Hardian (UNES Law Review, 2023)
ShopeeFood's online food delivery feature makes it easier for consumers not to have to laeve the house when they want to buy food. However, online transactions carried out using the ShopeeFood feature also have risks compared to direct transactions, where of course consumers can directly see the condition and quality of the product they want to purchase or can object or complaint directly. The main problem in this writing is the mismatch in orders received by ShopeeFood consumers. Of course, consumers feel disadvantaged by this happening. So consumers need legal certainty regarding responsibility for these losses in terms of the Consumer Protection Law. The research method used is normative legal research carried out using secondary data as legal material in the form of primary legal material. So the results of the research and discussion in this scientific journal will be able to answer the problems that occur, namely ShopeeFood provides a policy that consumers can submit requests for refunds or product replacements to Merchant or business actors through the platform provided by ShopeeFood. According to Law Number 8 of 1999 concerning Consumer Protection, if business actors do not carry out their obligations which are consumer rights, then consumers can sue the Merchant or business actor.